Our experience of treating dystrophic varus deformity of the femoral head in children - Denesyuk, Mykola; Panchyshyn, Viktor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
Experience in treatment of children with dystrophic varus deformity of the femoral neck during 25 years (1985–2009) is analysed. Attention is focused on 4 cases, which successfully underwent conservative treatment. Taking into account the positive results, it is recommended to use conservative treatment in patients with grade I of the disease, as well as with grade II, if their parents refuse the operation or the latter is contraindicated.